1986
DOI: 10.1073/pnas.83.16.5825
|View full text |Cite
|
Sign up to set email alerts
|

Activating mutations of the c-Ha-ras protooncogene in chemically induced hepatomas of the male B6C3 F1 mouse.

Abstract: Activated c-Ha-ras protooncogenes have recently been identified in the DNA of some spontaneous hepatic tumors found in 2-year-old B6C3 F1 mice. Activation of c-Ha-ras has now been demonstrated in DNA from well-differentiated hepatomas initiated by a single dose of carcinogen given to male B6C3 F1 mice at 12 days of age. DNA from each of 25 hepatomas, induced by N-hydroxy-2-acetylaminofluorene, vinyl carbamate, or l'-hydroxy-2',3'-dehydroestragole, contained transforming activity in the NIH 3T3 transfection ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
87
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(99 citation statements)
references
References 33 publications
11
87
1
Order By: Relevance
“…clusion is supported by the findings of mutational activation of ras proto-oncogenes in rat mammary carcinomas, mouse skin papilomas, and mouse hepatomas (3)(4)(5)(6)(7). (9,10).…”
Section: Carcinogenesis Is a Multistep Processsupporting
confidence: 60%
“…clusion is supported by the findings of mutational activation of ras proto-oncogenes in rat mammary carcinomas, mouse skin papilomas, and mouse hepatomas (3)(4)(5)(6)(7). (9,10).…”
Section: Carcinogenesis Is a Multistep Processsupporting
confidence: 60%
“…For these experiments, wild type and p21 Cip1 -null mice were treated with the DNA mutagen, urethane. Urethane has been shown to induce lung and liver tumors in mice by causing mutations in either the ras genes (tumor-sensitive mice) or other as yet unidentified genes (tumor-resistant mice, as used in the study described here) (Dragani et al, 1991;Mirvish, 1968;Nuzum et al, 1990;Wiseman et al, 1986). The second study examines tumor formation in MMTV/v-Ha-ras mice lacking p27 Kip1 rather than p21 Cip1 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that EtO exposure was capable of inducing A to T mutations . A number of other chemicals are also known to induce these mutations specifically in H-ras codon 61 (Vousden et al, 1986;Wiseman et al, 1986;Sills et al, 1999). As with A to G mutations, one potential mechanism for inducing A to T mutations would be through the formation of adenine adducts, particularly those that lead to depurination with insertion of an adenine opposite the apurinic site (Sagher and Strauss, 1983).…”
Section: Discussionmentioning
confidence: 99%